Cold water immersion (8°C) mediates greater reductions in lower limb blood flow and muscle temperature compared to whole body cryotherapy (-110°C) after endurance exercise - Mawhinney, C.; Low, D. A.; Jones, H.; Green, D. J.; Costello, J.; Gregson, W. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Cryotherapy is a widely used recovery method to limit exercise-induced muscle damage and soreness as well as functional deficits after strenuous exercise. Typical methods include cold-water immersion (CWI) and whole body cryotherapy (WBC), the former of which exposes the body to cold water temperatures (~10°C) for ~10 min, while the latter of which exposes the body to very cold air (-110-to -140 °C) for short durations (2-4 min). It is currently unknown which intervention mediates the greatest reduction in blood flow of the previously exercised limb(s). This is important given that reducing blood flow may directly limit muscle damage and function, thus aiding recovery. The aim of this study was, therefore, to compare the effects of ecologically valid CWI and WBC protocols on post-endurance exercise thermoregulatory, femoral artery and lower limb cutaneous blood flow responses. It was hypothesised that greater reductions in lower limb muscle temperature, femoral artery and cutaneous blood flow responses would occur after CWI. Methods: Ten males completed a continuous cycle exercise protocol at 70% maximal oxygen uptake until a core temperature of 38°C was attained. Participants were then exposed to CWI (8°C) for 10 min or WBC (-110°C) for 2 min in a randomised cross over design. Rectal and thigh skin, deep and superficial (3,2,1, cm) muscle temperatures, thigh and calf skin blood flow (laser Doppler flowmetry), superficial femoral artery blood flow (duplex ultrasound) and arterial blood pressure (automated sphygomomanometry) were measured prior to and for 40 min post cooling interventions. General linear model repeated measures ANOVA were used to evaluate responses to CWI and WBC conditions. Results: Greater reductions in thigh skin (CWI, -5.9±1.8°C; WBC, 0.2±0.5°C; P < 0.001) and superficial (CWI, -4.4±1.3°C; WBC, -1.8±1.1°C; P < 0.001) and deep (CWI, -2.9±0.8°C; WBC, -1.3±0.6°C; P < 0.001) muscle temperatures occurred after CWI. Decreases in femoral artery conductance were greater after CWI (CWI, -84±11%; WBC, -59±21%, P < 0.02) and greater thigh (CWI, -80±5%; WBC, -59±14%, P < 0.001) and calf (CWI, -73±13%; WBC, -45±17%, P < 0.001) cutaneous vasoconstriction was observed following CWI. Reductions in rectal temperature were similar between conditions (CWI, -0.6±0.4°C; WBC, -0.6±0.3°C; P = 0.98). Conclusion: CWI may be more effective than WBC in the treatment of exercise-induced muscle damage and injury rehabilitation by virtue of greater reductions in blood flow and tissue temperature.